Argos 1998 Information Days. - Argos, Brussel (Brussel : Argos, 1998)
André, Yaël ; Aubier, Stéphane ; Patar, Vincent ; Augustijnen, Sven ; Rogiers, Peter ; Baes, Pascal ; Bedel, Delphine ; Bergman, Marta ; Bianconi, Loredana ; Bismuth, Pierre ; Brosens, Peter ; Turmunkh, Dorjkhandyn ; Burki, Marie José ; Claerbout, David ; Clinckx, Christine ; Collard, Sandrine ; Crabeels, Cel ; Daems, Anne ; Dalemans Brothers ; Dans, Michael ; De Bemels, Antonin ; De Bisschop, Sarah ; De Block, Tommy ; de Boer, Manon ; Decaestecker, Ann ; De Clercq, Anouk ; Thornton, Leslie Tillotson ; De Decker, Koen ; De Felice, Daniela ; Defurne, Bavo ; De Gruyter, Jos ; Thys, Harald ; Vercammen, Stefan ; Delmotte, Monsieur ; Dementieva, Alexandra ; De Smedt, Christine ; Kruip, Germaine ; Malstaf, Vincent ; Opsomer, Els ; De Smet, Gery ; De Schuyteneer, Nicolas ; Patricia, Gélise ; Stampfli, David ; De Valck, Daniel ; Deligne, Anne ; Devos, Danny ; De Wit, Johan ; D'Haeseleer, Kurt ; D'Hondt, Lieve ; Lopes, Laone Dos Santos ; Jacob, Laurent ; Doukhan, Delphine ; Filmfabriek & Dziga ; Fersing, Eric ; Fol, Peter ; François, Michel ; Garcia, Dora ; Geronnez, Alain ; Gobyn, Luk ; Godin, Noël ; Gyuri, Macsai ; Hänzel & Gretzel ; Kandilaptis, Babis ; Kempenaers, Jan ; Krüger, Peter ; Messiaen, Gerrit ; Lai, Tamara ; Leroy, Annik ; Lizene, Jacques ; Lohlé, Dominique ; Londers, Veroni ; Lukomski, Xavier ; Fadden, Cybele Mac ; Martin, Isabelle ; Masyn, Dimitry ; Meyer, Eva ; Schaerf, Eran ; Malila, Lionel Mwe Di ; Nerinckx, Erik ; Neville, Mark leon ; de Beeck, Hans Op ; Opsomer, Els ; Pauwels, Eric ; Pauwels, Hugo ; Linden, Sabine Van der ; Pazienza, Claudio ; Persijn, Veerle ; Piccinato, Enzo ; Reinke, Steve ; Riche, Manu ; Robijns, Gert ; Scholten, Peter ; Simon, Philippe ; Scratchpetland ; Derycke, Fréderic ; Stidworthy, Imogen ; Suermondt, Robert ; etc.
Informatiedagen van 1998, Beursschouwburg, Brussel, 19 - 22/11/1998
boek